Pioneering TiO2/G-C3N4 Heterostructures for Enhanced Organic Pollutant Removal - Devagi, Kanakaraju; Danielson Ngo, Joseph; Pheodora Pamela, Natashya; Andrea, Pace (Wiley-VCH GmbH, 2025)
The remarkable synergy and versatility of TiO2/g-C3N4 compos-ites in photocatalytic applications, particularly for the removal of organic pollutants, have attracted considerable interest. This review provides a comprehensive overview of the modifications employed to enhance the properties of binary TiO2/g-C3N4 het-erostructures. The examination encompasses the modification of binary TiO2/g-C3N4 systems with various materials, includ-ing metal and nonmetal dopants, carbonaceous supports, and other semiconductors, among others. The effects of various parameters, such as synthesis methods, types of precursors, calcination procedures, and concentrations of precursors, are also correlated with the physicochemical properties and pho-tocatalytic performance of the materials. This in-depth explo-ration highlights TiO2/g-C3N4 advancements in engineering, more advanced and smart materials with enhanced visible light utilization and charge-transfer ability. Additionally, the review highlights the need for further investigation into the underlying mechanisms involved and the advancement of synthesis tech-niques that are both scalable and environmentally sustainable. Future directions for improving TiO2/g-C3N4-based heterostruc-tures are presented, with an emphasis on the potential to revolutionize photocatalysis for environmental remediation and sustainable energy generation.